DETERMINAN HARGA SAMURAI BONDS: PENGALAMAN INDONESIA - Nicodemus Simu (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2017)
This paper aim is to determine the impact of several macroeconomic variables on bond prices. The object of research is the Republic of Indonesia’s bonds denominated in Japanese Yen. Variables used in this research are the price of Samurai Bonds series RIJPY071 as the dependent variable, while the predictor variables are the level of Japanese inflation, exchange rate US$/JP¥ and Japanese interest rates. The data used in the research are monthly data from the period of January 2010 to August 2015 and the analysis tool used is multiple linear regression. The research concluded that the inflation rate has a positive influence on bond prices, both the exchange rate US$/JP¥ and the interest rates has a negative impact on bond prices.